Development of Interactive Video Media for Subtopic on Diseases or Disorders of the Bioprocess of the Digestive System in Grade XI High School - Kurnia Lisa; Ruqiah Ganda Putri Panjaitan; Titin Titin; Suprianto Salam (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The topic of diseases or disorders in the bioprocess of the digestive system is inherently abstract because the events cannot be directly observed, such as disruptions in the digestive tract within the abdominal cavity, making them difficult to understand. Interactive video serves as an audio-visual learning medium that is both engaging and interactive, thereby motivating learners to actively participate in the learning process. This study aims to develop an interactive biology video for the subtopic of diseases or disorders in the bioprocess of the digestive system for Grade XI high school students and to determine its suitability as a learning medium. The research and development stages follow Sugiono's (2021) framework, consisting of ten stages. However, this study focuses on the first five stages, which include identifying potential and problems, data collection, product design, design validation, and design revision. Data collection employed validation sheets as instruments, and data analysis techniques involved qualitative and quantitative data analysis. The validation results indicated an average CVR and CVI score of 1.00 for format, content, and language aspects, which falls into the valid category. In conclusion, the interactive video media developed in this study is deemed suitable for use as a learning medium in Grade XI high school classrooms, specifically for the subtopic of diseases or disorders in the bioprocess of the digestive system.